Hypermarket retailing expansion as a hub of socio-economic development in Malaysia - Hassan, Hasliza; Mahdee, Junainah; Sade, Abu Bakar; Rahman, Muhammad Sabbir (North Carolina Central University School of Business, 2015)
The majority of Malaysians prefer to go to a hypermarket to purchase the basic necessities for their household. Due to the high acceptance of this modern retailing concept, hypermarket retailing has had an incredible impact with respect to the overall retailing industry in Malaysia. This research explores the advantages of having more hypermarket outlets for the society as a whole. The research is mainly based on general observations and is supported with secondary reviews from previous research scholars. It is expected that those locations that are less developed will experience a positive impact by having more hypermarket outlets within the area. This is because the hypermarket is able to stimulate the overall economic development and, at the same time, improve the socio-economic level of the society.